Diabetes Risk Score in a Young Student Population in Jordan: A Cross-Sectional Study - Abdel-Ellah Al-Shudifat; Amjad Al-Shdaifat; Ahmad Ali Al-Abdouh; Mohammad Ibrahim Aburoman; Sara Mohammad Otoum; Amro Ghaleb Sweedan; Ibrahim Khrais; Ibrahim Hisham Abdel-Hafez; Asgeir Johannessen (Journal of Diabetes Research)
Background. The Middle East is the home to the most obese population in the world, and type 2 diabetes mellitus is endemic in the region. However, little is known about risk factors for diabetes in the younger age groups. Methods. The Finnish Diabetes Risk Score (FINDRISC) is a simple, validated tool to identify persons at risk of diabetes. We investigated students at Hashemite University in Jordan with FINDRISC and measured fasting plasma glucose in those who were categorized in the high-risk group. Results. Overall, 1821 students (881 [48.4%] female) were included in the study. Risk factors for diabetes were common: 422 (23.2%) were overweight or obese and 497 (27.3%) had central obesity. Using the FINDRISC score, 94 (5.2%) students were at moderate risk and 32 (1.8%) at high risk of diabetes. The mean FINDRISC score was significantly higher in men than women (5.9 versus 5.4; p=0.002). Twenty-eight students in the high-risk group had a subsequent plasma glucose measurement, and 8 (29%) of them fulfilled the diagnostic criteria for diabetes. Conclusions. Risk factors for diabetes were common in a young student population in Jordan, suggesting that preventive measures should be initiated early in adulthood to turn the diabetes epidemic in the region.